FRI0394 The role of d-dimer test as a screening tool for venous thromboembolism in patients with systemic lupus erythematosus as compared to matched control subjects - Oh, Y.J.; Park, E.H.; Park, J.W.; Song, Y.W.; Lee, E.B. (Annals of the rheumatic diseases, 2018)
Backgroundd-dimer test is widely used as a screening tool for venous thromboembolisms (VTE). Meanwhile, d-dimer can increase in various conditions including severe infection, and inflammation. However, it has been rarely reported whether d-dimer test is useful for screening of VTE in systemic lupus erythematosus (SLE) patients.ObjectivesWe evaluated the role of d-dimer test as a screening tool for VTE in patients with SLE, compared to age-, and sex-matched non-autoimmune disease subjects.MethodsIn this retrospective cohort study, a total of 283 SLE patients and 1132 age-, and sex-matched control subjects (those who had no rheumatic diseases) who underwent d-dimer test as a screening test for VTE were enrolled at Seoul National University Hospital between January 2000 and July 2017. VTE was defined to be present when a thromboembolism was proven in imaging studies which included computed tomography, lung perfusion scan or duplex ultrasonography. Predictive value of d-dimer test for VTE was compared between SLE patients and control subjects by calculating area under the curves (AUC) in receiver operating characteristics (ROC) curves of d-dimer test. Finally, the usefulness of d-dimer test was evaluated in different subsets of SLE patients by analysing ROC curves.ResultsThe mean (SD) age of the 283 SLE patients was 36.8 (13.5) years and that of 1132 control subjects was 38.2 (12.8) years. The mean (SD) plasma level of d-dimer was 2262.1 (3794.5) ng/ml in SLE patients, while it was 1087.5 (5063.1) ng/ml in the control group (p<0.001). The incidence of VTE was significantly higher in SLE patients than the controls (12.7% vs. 5.8%, p<0.001). When the cut-off value of d-dimer test was set to 500 ng/ml, the AUC for VTE was only 0.614 in SLE patients, while it was 0.891 in the control group, suggesting that d-dimer test may not be useful as a screening tool for VTE in SLE patients. When the SLE patients were divided according to the presence of antiphospholipid antibodies (APS Abs), the AUC value for VTE was 0.788 in patients who didn’t have APS Abs but it was only 0.556 in patients who had APS Abs.Abstract FRI0394 – Figure 1ROC curves in control and SLE group (cut-off value of d-dimer = 500 ng/ml)Conclusionsd-dimer test cannot predict VTE in SLE patients as accurately as in general population. In SLE patients, d-dimer’s diagnostic capability for VTE is even lower in the presence of APS Abs.References[1] Chung WS, Lin CL, Chang SN, et al. Systemic lupus erythematosus increases the risks of deep vein thrombosis and pulmonary embolism: a nationwide cohort study. J Thromb Haemost2014;12:452–8.[2] Avina-Zubieta JA, Vostretsova K, De Vera MA, et al. The risk of pulmonary embolism and deep venous thrombosis in systemic lupus erythematosus: A general population-based study. Semin Arthritis Rheum2015;45:195–201.[3] Kristoffersen AH, Ajzner E, Rogic D, et al. Is D-dimer used according to clinical algorithms in the diagnostic work-up of patients with suspicion of venous thromboembolism? A study in six European countries. Thromb Res2016;142:1–7.[4] Ahlehoff O, Wu JJ, Raunso J, et al. Cutaneous lupus erythematosus and the risk of deep venous thrombosis and pulmonary embolism: A Danish nationwide cohort study. Lupus2017;26:1435–9.[5] Wells PS, Ihaddadene R, Reilly A, et al. Diagnosis of Venous Thromboembolism: 20 Years of Progress. Ann Intern Med2018;168:131–40.Disclosure of InterestNone declared